(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the factors associated with the profile and sociodemographic distribution of patients with dyslipidemia treated at the Basic Health Units in the municipality of Guanambi/BA. Methods: This is a descriptive research, with quantitative field analyses. The research subjects were 63 dyslipidemic patients, followed up by Basic Health Units in the city, randomly selected and a questionnaire with direct and objective questions related to the interests of the study was applied. The procedure used respected and considered the international standards of experimentation with humans, having been approved by the Ethics Committee. Results and Conclusion: It was evidenced that dyslipidemia is more present in individuals over 65 years of age, with a high percentage of sedentary and overweight subjects, with simvastatin being the most used drug during treatment. It was also noticed the occurrence of side effects in a small portion of the population surveyed.